Thinking beyond Privacy Calculus: Investigating Reactions to Customer Surveillance. Issue 1 (May 2020) - Plangger, Kirk; Montecchi, Matteo
As interactive technologies become more pervasive, firms are increasingly conducting customer surveillance—the acquisition, usage, and storage of consumers' personal data—more covertly and with fewer resources. Privacy calculus—the rational decision to disclose personal data—has dominated the literature to explain rational or calculated reactions to customer surveillance, however, not all reactions can be explained by rational processes. This article advances our understanding of these reactions beyond the privacy calculus concept by proposing attitudes toward customer surveillance. Based on levels of consumer privacy and consumer value concerns, these attitudes are associated with four archetypes—pragmatists, protectionists, capitalists, and apathists. By understanding these attitudes, researchers and managers can gain insight into the diversity of consumers' concerns regarding both consumer privacy and consumer value in order to better explain observed marketplace behaviors.